2022
DOI: 10.3390/pathogens11040443
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Enteritidis Subunit Vaccine Candidate Based on SseB Protein Co-Delivered with Simvastatin as Adjuvant

Abstract: Salmonella enterica serovar Enteritidis (S. Enteritidis) is an important zoonotic pathogen that can lead to diarrhea and systemic infections in humans and mortality in animals. This is a major public health issue worldwide. Safe and effective vaccines are urgently needed to control and prevent Salmonella infection. Subunit vaccines are safe and provide targeted protection against Salmonella spp. Here, we developed and evaluated an S. Enteritidis subunit vaccine candidate, the rHis-SseB adjuvant with simvastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…5 B–D). It is known that IgG1/IgG2a ratio between 0.5 and 2.0 implies a balanced Th1/Th2 polarization, while that of below/equal to 0.5 or above/equal to 2.0 indicates Th1 or Th2 polarizations, respectively 35 . Our results indicated a balanced Th1/Th2 polarization for groups receiving TLR7 agonists (R837 or Aldara) by SC immunization (RP + AP + R837, RP + AP + AL or RP + R837).…”
Section: Discussionmentioning
confidence: 99%
“…5 B–D). It is known that IgG1/IgG2a ratio between 0.5 and 2.0 implies a balanced Th1/Th2 polarization, while that of below/equal to 0.5 or above/equal to 2.0 indicates Th1 or Th2 polarizations, respectively 35 . Our results indicated a balanced Th1/Th2 polarization for groups receiving TLR7 agonists (R837 or Aldara) by SC immunization (RP + AP + R837, RP + AP + AL or RP + R837).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this study has been shown to confer cross-protection against S. Infantis (serotype C strains) [192]. However, despite the ability of live-attenuated vaccines to stimulate both cell-mediated and mucosal immune responses, the biosecurity risk of virulence reversal of the live vaccine strain is the major drawback of live-attenuated vaccines [193]. 6.9.2.…”
Section: Bacteriophagesmentioning
confidence: 97%
“…Several studies have identified Salmonella subunit vaccine antigens that can be used for immunization. 143 Recombinant OMPs are being studied extensively as subunit vaccines for various diseases. Because subunit vaccines solely possess the antigen proteins and not the complete pathogen, they are highly immunogenic and considered safe.…”
Section: Resistance In Other Organismsmentioning
confidence: 99%
“…In recent years, the development of subunit vaccines targeting OMPs has become an increasingly popular field of research. Several studies have identified Salmonella subunit vaccine antigens that can be used for immunization . Recombinant OMPs are being studied extensively as subunit vaccines for various diseases.…”
Section: Application Of Omps and Efflux Pumps For Possible Therapeuti...mentioning
confidence: 99%